2003
DOI: 10.1016/s0378-1097(03)00212-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon repression of cellobiose dehydrogenase production in the white rot fungusTrametes versicoloris mediated at the level of gene transcription

Abstract: Cellobiose dehydrogenase (CDH) production in Trametes versicolor is induced in the presence of cellulose, but decreases when additional carbon sources such as glucose and maltose are added to the fungal cultures. Using T. versicolor-specific cdh primers in a reverse transcription-polymerase chain reaction-based approach, it appears that this repression in CDH production is being mediated at the level of gene transcription. When a 1.6-kb upstream region of the T. versicolor cdh gene was cloned and sequenced, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As postulated for cellulases and hemicellulases, the absence of CDH could be explained by the presence of traces of glucose, since the expression of the T. versicolor orthologue is also strongly regulated at transcriptional level by carbon catabolite repression mechanisms [67].…”
Section: Resultsmentioning
confidence: 92%
“…As postulated for cellulases and hemicellulases, the absence of CDH could be explained by the presence of traces of glucose, since the expression of the T. versicolor orthologue is also strongly regulated at transcriptional level by carbon catabolite repression mechanisms [67].…”
Section: Resultsmentioning
confidence: 92%
“…The repression of CDH biosynthesis both by glucose and by the disaccharide maltose is mediated at the level of transcription. A number of putative Cre-A or Cre1 repressor-like binding sites were detected in a 1.6-kb upstream region of the T. versicolor cdh gene [31]. These sites displayed high sequence similarity with consensus sites for binding repressor proteins in Aspergillus and Trichoderma species, and it was concluded that these sites might be responsible for the repressive effect on cdh transcription.…”
Section: Production Of Cdh In Basidiomycetesmentioning
confidence: 96%
“…Further, it was shown that CDH production in both Grifola frondosa [30] and T. versicolor [31] is subject to carbon catabolite repression. Such metabolic regulation is interpreted as an energy-saving response whereby readily metabolisable carbohydrates, such as glucose, repress the synthesis of enzymes involved in the catabolism of alternative carbon sources.…”
Section: Production Of Cdh In Basidiomycetesmentioning
confidence: 99%
“…1A in the glucose cultures laccase activity first appeared on day 4 (372 U/l) and then it sharply increased to 4304 U/l on day 7 reaching its peak on the last cultivation day (7974 U/l). CDH was not detected, since glucose inhibits CDH expression [21]. As for cellulose cultures (Fig.…”
Section: Enzyme Productionmentioning
confidence: 86%